Kajian Yuridis Tentang Perizinan Pedagang Kaki Lima Dibahu Jalan Di Kota Pangkalpinang - Dhea Preyanita Oktari; Ernest Violita; Adilla Riski; Sigit Nugroho (CV. Multi Kreasi Media, 2023)
Street vendors (hereinafter abbreviated as PKL) are informal sector traders who usually use public spaces, use urban infrastructure, and use both temporarily or permanently commercially which can disrupt public order and public peace as regulated in regional Regulation No. 7 of 2019 concerning the Organization of Public Order and public peace (hereinafter abbreviated as Perda No. 7 of 2019). The purpose of this study was to determine the effectiveness of Pangkalpinang regional Regulation Number 7 of 2019 related to the arrangement of street vendors in Pangkalpinang City and to determine the factors that are obstacles in the arrangement of street vendors in Pangkalpinang City. Using a qualitative approach. The research method used is descriptive qualitative research methods. The descriptive nature of qualitative research explains that it aims to provide a systematic, accurate and factual description of a fact, characteristic or relationship between the phenomena studied. The results of this study are based on regional Regulation No. 7 of 2019 concerning the Organization of Public Order and public peace that there are still many street vendors who violate the provisions of the regional regulation due to street vendors who do not want to move from their trading locations and lack of Law Enforcement facilities and infrastructure in carrying out law enforcement against street vendors.